Gastrodia gunatillekeorum (Gastrodieae, Epidendroideae, Orchidaceae), a new species from a lowland rainforest of Sri Lanka - Bandara, Champika; Priyankara, Theja; Atthanagoda, Anusha G.; Lakkana, Tithira; Ediriweera, Sisira; Kumar, Pankaj (Phytotaxa, 2020)
Gastrodia gunatillekeorum, a new species in the family Orchidaceae, is described and illustrated from a tropical lowland rainforests of Sri Lanka. It is morphologically close to G. spatulata which is endemic to Indonesia owing to the white flower front with yellowish-orange colour on the inner wall of perianth tube and free part of perianth tube reflexed backwards. However, these two species can be very well differentiated on the basis of spathulate to linear petals which are shorter than sepals, fused only at the base and present inside the perianth tube; labellum elongate-elliptic and column broadest in the middle part in G. spatulata, whereas petals as long as sepals with apical 1/3rd part free (rest fused with sepals) and reflexed backwards, labellum rhomboid in shape, column broadest towards the apex in G. gunatillekeorum. Taxonomic account, line drawing, color photographs and conservation assessment are provided for the new species.